The Materials and Techniques of William Robinson. Issue 2 (2nd July 2016) - Theobald Clark, Sophie; Osmond, Gillian
Abstract : The William Robinson Gallery is the only gallery in Australia dedicated to the work of a living artist. The significance of this collection in conjunction with the artist's co-operation has provided impetus for a research project dedicated to compiling a technical art history of Robinson's materials and techniques for posterity, and to inform long-term conservation of the artist's works. Artist's interviews, technical analysis and an online conservation survey reveal that Robinson's materials and techniques evolved in response to the changes in his subject matter and also highlighted discrepancies where the presence of certain materials, or lack thereof, was unintended by the artist. Some of these materials, such as zinc stearate, are associated with deterioration in the artists' work. Samples from 16 paintings were investigated using a combination of analytical techniques including optical microscopy, ultraviolet fluorescence photography, Fourier Transform Infrared microspectroscopy, Scanning Electron Microscopy with Energy Dispersive X-ray analysis and Synchrotron source Fourier Transform Infrared microspectroscopy.